Features of development of coordination abilities features of athletes in sports aerobics in initial training - Bodrenkova, I.A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : to develop theoretically and experimentally justify the methodology of development of coordination abilities of athletes aged 7-9 years involved in sports aerobics. Material : the study involved 20 participants (7-9 years). 8 athletes performed the test tasks. The choice of tests carried out on the basis of the analysis of the dominant motor mode competition exercises. Results : It was found that the coordination abilities are necessary in the development of speed, density, and the number of running technical elements. With more than a significant increase in performance test tasks that characterize: musicality, coordination, dynamic balance. The basic tools, methods, techniques, and requirements for the exercises. The level of development of coordination abilities. Conclusions : the author's method of development of coordination abilities include: rational choice of means and methods of training impact on their similarities and differences with the target competitive activity.